2007
DOI: 10.1016/j.jneuroim.2006.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Polyreactive myelin oligodendrocyte glycoprotein antibodies: Implications for systemic autoimmunity in progressive experimental autoimmune encephalomyelitis

Abstract: Two myelin oligodendrocyte glycoprotein ) monoclonal antibodies (mAbs) were produced from an A.SW mouse with progressive experimental autoimmune encephalomyelitis. Polyreactivity/specificity of the mAbs was demonstrated by ELISA. Functionality and a potential role in pathogenesis of systemic autoimmunity were demonstrated in vitro in a lymphocytotoxicity assay and in vivo upon injection into naïve mice. Injection of MOG mAb producing hybridomas into naïve mice resulted in immunoglobulin deposition in kidneys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…Previously, we reported that two MOG 92–106 anti-bodies produced by two hybridoma cell lines were NAA of the IgM isotype, which reacted not only with the initiating antigen, but also protein isolated from organs outside the CNS and antigens associated with systemic autoimmune disease [33], such as dsDNA and histone H1a [41]. If these NAA contribute significantly to the amount of IgM antibodies reactive with MOG 92–106 and dsDNA, depletion of the major producer of these antibodies, B-1 cells, should drastically reduce serum titer of MOG 92–106 and dsDNA antibodies of the IgM isotype.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we reported that two MOG 92–106 anti-bodies produced by two hybridoma cell lines were NAA of the IgM isotype, which reacted not only with the initiating antigen, but also protein isolated from organs outside the CNS and antigens associated with systemic autoimmune disease [33], such as dsDNA and histone H1a [41]. If these NAA contribute significantly to the amount of IgM antibodies reactive with MOG 92–106 and dsDNA, depletion of the major producer of these antibodies, B-1 cells, should drastically reduce serum titer of MOG 92–106 and dsDNA antibodies of the IgM isotype.…”
Section: Resultsmentioning
confidence: 99%
“…I.c. injection of the MOG 92–106 antibody producing hybridomas into naïve mice resulted in antibody deposition and demyelination in the CNS [33]. This led us to hypothesize that NAA were involved in the disease progression and demyelination in A.SW mice with MOG 92–106 induced P-EAE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A.SW mice sensitized with amino acids 92-106 from myelin oligodendrocyte glycoprotein (MOG) developed a PP form of experimental autoimmune encephalomyelitis (EAE), an autoimmune animal model of MS, which is traditionally considered to be organ-specific [13,14]. Surprisingly, mice with PP-EAE had antibody deposition in the glomeruli of their kidneys [13,14].…”
Section: Introductionmentioning
confidence: 99%